Creating leaner supply chains - Hines, Peter (Henry Stewart Talks, 2010)
The lean business model, Extended Enterprise, Creating lean supply chains, Tiered supply structure, Numbers of suppliers, Asset specificity, Maximum buy strategy, Bilateral Design, Supplier innovation, Relationships, Supplier measurement, Category management, Supplier associations, The Toyota production system